Future of coal in rural household energy mix in China - Shuyan CAO; Qinfei XU; Dongwei ZHANG; Lan HUANG; Fei LONG; Wei ZHANG (Meitan xuebao, 2023)
Carbon neutrality target triggers the acceleration of China's rural energy revolution and energy transition. It is an irreversible trend that coal will phase out Rural Household Energy Mix (RHEM) in the long run. Problem is how coal will phase down and phase out in an orderly, effective, fair and high-quality way. National rural household energy consumption of all types is reviewed and related carbon emission accounted to manifest the evolvement of coal’s role, status and impacts in China’s RHEM since 1949. Household-level survey carried out in rural Beijing has discovered problems and challenges in the phasing out coal due to policy enforcement. Exergy is further assessed and predicted. The future role and contribution of coal among RHEM is identified for outlining coal’s phase out path by considering the resilience, economy and differentiated bottlenecks of carbon-neutral RHEM from the three-dimensional perspective of exergy, base energy context and comparative comprehensive cost-benefit calculation of energy substitution. The conclusions are as follows: ① Per capita energy consumption and exergy demand will continue to increase in coming years, and the per capita electricity consumption peak in a full electrification mode of RHEM is conservatively estimated to be about 5 000 kW·h. ② In the long run, rural household energy electrification has the characters of carbon neutrality, renewability and marketization. The coal revolution in RHEM, pursuing an improved cleaner and affordable energy pattern, consists of sustainable energy replacing coal and coal replacing biomass fuels. Before rural green energy market fully developed, coal is still the “ballast” for rural energy security. ③ In accordance with regional differences, it is wise to resort to five sub-path combinations belonging to three coal phaseout paths, that is, coal neutrality (improved stove technology and let the coal be), coal substitution (including coal replacement of primary biomass; clean coal upgrading) and coal substituted (inclusive of voluntary and mandatory phaseout of coal). It is anticipated that rural residents will enjoy a modern carbon-neutral energy system with resilience and fairness in future China.